APLIKASI CIRCULATING FLUIDISED BED (CFB) UNTUK PENINGKATAN EFISIENSI PEMBAKARAN - R. Herry Supriyanto (Jurnal Energi dan Lingkungan (Enerlink), 2005)
Currently, the circulating fluifized bed combustion (CFBC) technology for coal combustion remains developed for its advantages such as flexibility against coal quality, high combustion efficiency and relatively lower SO2 and NOx emission. This article discusses the results of a study upon the influence of operational parameter toward combustion efficiency and SO2 and NOx emission on a 100kW CFBC unit. Operational parameters examined include temperature, air excess, secondary air and speed of superficial gas. Results obtained shows that the tested operational parameters were effectively affects the combustion efficiency and SO2 and NOx emission.Kata kunci: Gasifier, circulating, katalis